Mouse models of mineral bone disorders associated with chronic kidney disease - Zaloszyc, Ariane; Bernardor, Julie; Bacchetta, Justine; Laverny, Gilles; Schmitt, Claus P. (International journal of molecular sciences, 2023)
Patients with chronic kidney disease (CKD) inevitably develop mineral and bone disorders (CKD-MBD), which negatively impact their survival and quality of life. For a better understanding of underlying pathophysiology and identification of novel therapeutic approaches, mouse models are essential. CKD can be induced by surgical reduction of a functional kidney mass, by nephrotoxic compounds and by genetic engineering specifically interfering with kidney development. These models develop a large range of bone diseases, recapitulating different types of human CKD-MBD and associated sequelae, including vascular calcifications. Bones are usually studied by quantitative histomorphometry, immunohistochemistry and micro-CT, but alternative strategies have emerged, such as longitudinal in vivo osteoblast activity quantification by tracer scintigraphy. The results gained from the CKD-MBD mouse models are consistent with clinical observations and have provided significant knowledge on specific pathomechanisms, bone properties and potential novel therapeutic strategies. This review discusses available mouse models to study bone disease in CKD.